Apexification in a traumatized tooth with mineral trioxide aggregate: an interesting case report of root formation - Margarete A. G. Melo GUIMARÃES; Héctor RODRIGUES; Stéphanie Quadros TONELLI; Daniel Sousa PARDINI; Frank Ferreira SILVEIRA (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Mineral trioxide aggregate (MTA) has been indicated for apexification because it has desirable properties such as excellent biocompatibility, low solubility and dimensional stability. This procedure consists of inducing root apex formation in teeth with incomplete root formation. This article reports a case of trauma in a young dental element, with necrotic pulp and incomplete root formation. For its treatment, apexification with white MTA was performed, which showed excellent results in inducing the continuity of root formation with mineralized tissue in the apical portion. Therefore, MTA is a viable option for apexification, bringing as its main advantage, faster treatment and immediate coronary rehabilitation of the dental element.